Two new lithophytic species of the genus Peperomia (Piperaceae) from the state of Chiapas, Mexico - García-Martínez, Roberto; Beutelspacher-Baigts, Carlos R.; Callejas-Posada, Ricardo; Mathieu, Guido (Phytotaxa, 2018)
Two new species of Peperomia from the state of Chiapas, Mexico, P. asarifolioides García-Martínez & Beutelspacher and P. pseudoasarifolia Callejas & G.Mathieu, are described and illustrated. Both are morphologically close to Peperomia asarifolia Schltdl & Cham. and specimens of both new species have been identified as that species in the past. However, recent field work and thorough herbarium study revealed them to be distinct species.